Infection of Artemia sp. by Lymphocystis disease virus (LCDV) - Jiménez Valverde, Estefanía; Cano, Irene; García-Rosado, Esther; Alonso-Sánchez, María del Carmen; Borrego-García, Juan José; Castro-López, María Dolores (My University, 2013)
In the present work, different developmental stages of Artemia sp. (metanauplius, juvenile and adult) were experimentally infected with LCDV by immersion. Results of viral quantification (both by qPCR and cell-culture viral titer determination) and expression showed that LCDV establishes a productive infection in Artemia, at least under experimental conditions, extending the host range of this virus to crustaceans.
Keywords: Artemias; LCDV; Artemia